World Statistics Pocketbook 2021 - United Nations Department of Economic; Social Affairs (United Nations, 2021)
The World Statistics Pocketbook is an annual compilation of key statistical indicators prepared by the United Nations Statistics Division of the Department of Economic and Social Affairs. Topics covered include: agriculture, balance of payments, education, energy, environment, food, gender, health, industrial production, information and communication, international finance, international tourism, international trade, labour, migration, national accounts, population and prices.